About degassing of the Earth - Gordienko, V. V. (Geofizicheskiy Zhurnal, 2019)
Degassing of the Earth has attracted great attention of geologists in recent years. The range of opinions on various aspects of the problem is very large. Some of them from the author’s point of view are based on unreasonable assumptions or misinterpreted facts. The article attempts to consider briefly the most controversial aspects of the concept, using analytical methods, the possibility of which gives the application of the advection-polymorphic hypothesis, and some results obtained with its help. It was necessary to bring data on heat and mass transfer in the tectonosphere, for which the determining influence on geodynamics was proved. The main attention is paid to the amount of transported matter and energy consumed by deep processes. It is shown that the parameters of the mass flow transferring the gas component from the mantle to the crust and the atmosphere established by isotope-geochronometric data and the scheme of deep processes in the hypothesis used are identical. The parameters of the degassing process under magmatism and circulation of fluids during the formation of deposits of ores and hydrocarbons are considered. It is shown that the energy transferred by them is incommensurable with the energy required for geodynamics. The formation of fluids in crustal rocks during activation is analyzed. More details of other phenomena studied the formation of hydrogen fluid and its role in the creation of hydrocarbon de-posits. The total number of crustal fluids can be matched to that fixed during degassing of the Earth. The participation of fluids from the upper mantle is beyond doubt, they arise in the process of activation of the tectonosphere, heat and mass transfer accompanied by partial melting of rocks. But their number is insignificant in comparison with the crustal fluids. The idea of the absence of conditions for the formation of fluids suitable for removal to the upper mantle and crust, in the lower mantle and core, is substantiated. Velocity sections are presented, which are given in support of this removal. As the regions for this control, transitional zones between continents and the Pacific Ocean are selected, where velocity disturbances can be maximum. Unreliability of the anomalies in the velocity of seismic waves in the lower mantle according to seismic tomography is shown.